A Mathematical Description of the Agricultural Fields of the Acolhua Codices Vergara and Santa María Asunción. Issue 4 (December 2021) - Jorge, María del Carmen; Garza-Hume, Clara Eugenia; Chávez, Ramiro
Abstract : We carry out a mathematical analysis of the quadrilateral fields from Codex Santa María Asunción and compare it with similar previous results from Codex Vergara, as well as analyze fields with more than four sides from both codices. We also provide a computational tool to draw all the possible shapes of the fields. Finally, we use the concept of maximum area to test the feasibility of the areas recorded in the codices and conclude that the Acolhua were very good surveyors.